Antifungal Activity of Some Essential oil of Aromatic Plants Against Post Harvest Disease of Grapes (Vitis vinifera) - Bista, Urmila; Chaudhary, Dinesh; Bist, Dhan Bahadur; Joshi, Anand Prakash (AMC Journal (Dhangadhi), 2024)
As being highly perishable fruit Grapes quality and shelf life is affected by various factors during postharvest among them common loss in caused by fungi. An in-vivo study was carried out to test possibility of the use of some plant essential oil of Cinnamomum tamala, Cymbopogon flaxuosus, Cinnamomum tenuiple, Mentha spicata and Eucalyptus citriodora to reduce post-harvest loss induced by fungi. Aspergillus niger was most frequent fungal pathogen isolated from grapes collected from local markets of Dhangadhi city. Pathogenity test was confirmed by inoculating the pathogen in healthy grapes. Essential oils (EOs) of five essential oil extracted by hydro-distillation using Clevenger oil extracting apparatus. Using various concentration (40, 20, 10, 5 and 2.5 µl/ml) of Eos the fungi was treated by using poisoned food technique. Significant (p